The emerging role of EID in Asia Pacific in greening the economies - Chiu, Anthony S.F. (Animo Repository, 2011)
There have been several eco-industrial development (EID) initiatives in Asia Pacific since 1997. These EID initiatives, adopting the industrial ecology (IE) concept, have taken various approaches to sustainable development in their regions. Some have taken the form of eco-industrial estate while others have taken the structure of a city or town. This paper simplifies these various approaches into a generic structure, and presents four developmental stages describing how these EID models advanced from lower stages of plainly environmental protection to higher stages of a green economy. Three categories of national/regional EID involvement are also proposed in this study. Finally, it is argued that Asia Pacific economies belonging to different developmental stages need to assess their respective strengths in order to craft their competitive green economy strategies for a promising world market share.